Sparta; Mantinea and Parrhasia; Elis and Lepreon: Politics and Autonomy in 421-418 BC - Roy, James (Classica et Mediaevalia, 2022)
Following the end of the Archidamian war Sparta intervened in Parrhasia and at Lepreon. The interventions weakened Mantinea and Elis, two states that caused difficulties for Sparta, but besides Realpolitik there were also questions of law, and the Spartans, though anxious to achieve strategic advantages, were careful to act with proper legal authority. Sparta declared both Parrhasia and Lepreon autonomous, but autonomy did not mean the same status in the two cases. Since knowledge of these incidents comes mainly from Thucydides’ Book 5, the argument depends heavily on interpretation of Thucydides’ text.